2009
DOI: 10.1002/art.24301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronic acid in symptomatic hip osteoarthritis: A multicenter, randomized, placebo‐controlled trial

Abstract: Objective. To evaluate the efficacy and tolerability of a single intraarticular (IA) injection of hyaluronic acid (HA) for the treatment of hip osteoarthritis (OA).Methods. A multicenter, randomized, parallelgroup, placebo-controlled trial was conducted over 3 months. Patients (older than 30 years) with symptomatic hip OA (pain score of >40 mm on a visual analog scale [VAS]) and a Kellgren/Lawrence grade of 2 or 3 were randomly assigned to receive 1 fluoroscopically guided IA injection of HA (2.5 ml) or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 28 publications
1
79
0
7
Order By: Relevance
“…One study showed no significant difference between HA (3 injections), saline and corticosteroid use at 3-month follow-up, despite some level of clinical benefit with corticosteroid and HA use [59]. Findings from an uncontrolled study by Conrozier et al [60] suggested that a single injection of HA was efficacious in hip OA; however, a recent, randomised, placebo-controlled trial in 85 patients showed no significant difference between placebo and a single intra-articular injection of HA for reduction in pain at 3-month follow-up [61]. Clearly, large well-controlled trials of HA in hip OA are warranted.…”
Section: Knee Oamentioning
confidence: 96%
“…One study showed no significant difference between HA (3 injections), saline and corticosteroid use at 3-month follow-up, despite some level of clinical benefit with corticosteroid and HA use [59]. Findings from an uncontrolled study by Conrozier et al [60] suggested that a single injection of HA was efficacious in hip OA; however, a recent, randomised, placebo-controlled trial in 85 patients showed no significant difference between placebo and a single intra-articular injection of HA for reduction in pain at 3-month follow-up [61]. Clearly, large well-controlled trials of HA in hip OA are warranted.…”
Section: Knee Oamentioning
confidence: 96%
“…If compared to placebo, it is not clear whether HA is more effective in the treatment of hip OA. Richette et al 24 performed a single injection of HA or placebo. VAS and WOMAC were evaluated after 3 months and compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular injection of hyaluronic acid is still controversial in the management of hip osteoarthritis (OA), as its efficacy has not been clearly established. 3,[5][6][7][8][9] More recently, intra-articular injections of platelet-rich plasma (PRP) have been proposed but presently there is a paucity of data supporting its wide use in clinical practice.…”
Section: Intra-articular Aspirations and Injectionsmentioning
confidence: 99%